2005
DOI: 10.1021/bm049314v
|View full text |Cite
|
Sign up to set email alerts
|

CaCO3Biomineralization:  Acidic 8-kDa Proteins Isolated from Aragonitic Abalone Shell Nacre Can Specifically Modify Calcite Crystal Morphology

Abstract: Acidic proteins from many biogenic minerals are implicated in directing the formation of crystal polymorphs and morphologies. We characterize the first extremely acidic proteins purified from biomineralized aragonite. These abalone nacre proteins are two variants of 8.7 and 7.8 kDa designated AP8 (for aragonite proteins of approximately 8 kDa). The AP8 proteins have compositions dominated by Asx (∼35 mol %) and Gly (∼40 mol %) residues, suggesting that their structures have high Ca 2+ -binding capacity and bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
182
0
4

Year Published

2005
2005
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(191 citation statements)
references
References 46 publications
5
182
0
4
Order By: Relevance
“…It should be noted that step velocity data in these studies were obtained at slightly different supersaturation and ionic strength conditions (6,7). The most potent additive was AP8-␣, an 8-kDa, highly acidic protein extracted from the mineralized tissue of abalone (10). At the 0.1-M level of this protein the acceleration was 150%, a value 10-fold more than for Asp-6, the most potent of the very small peptides (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that step velocity data in these studies were obtained at slightly different supersaturation and ionic strength conditions (6,7). The most potent additive was AP8-␣, an 8-kDa, highly acidic protein extracted from the mineralized tissue of abalone (10). At the 0.1-M level of this protein the acceleration was 150%, a value 10-fold more than for Asp-6, the most potent of the very small peptides (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A probable relationship between the chemical features of biomolecules and crystal growth control is supported by many observations showing that proteins isolated from sites of biomineralization in tissues are unusually enriched in highly acidic amino acids, notably aspartic acid and also glutamic acid (9)(10)(11)(12)(13). The Asp-rich motifs have been postulated to function by preferentially binding to cations such as Ca 2ϩ (14) during the controlled formation of minerals such as calcite (12).…”
mentioning
confidence: 96%
“…Characteristic Raman bands for calcite and aragonite were assigned as described elsewhere. [6][7][8][9] Calcite and aragonite are two common polymorphs of CaCO3 observed as biominerals.Stony coral forms needle-like aragonite crystals, but soft coral forms only calcite crystals. The protein-induced chemical structure in calcified organisms is an important factor contributing to their growth, but until now no direct evidence has been reported.…”
mentioning
confidence: 99%
“…Characteristic Raman bands for calcite and aragonite were assigned as described elsewhere. [6][7][8][9] Calcite and aragonite are two common polymorphs of CaCO3 observed as biominerals.…”
mentioning
confidence: 99%
“…Control experiments revealed that the presence of calcite crystal wires only occurred in the wells containing both the [Fe(Biot 2 -terpy) 2 ] 2+ complex and Sav building blocks. Calcite microcrystals have been grown on a wide variety of templates, including Kevlar, [54][55][56] nylon, [57] self-assembled monolayers, proteins, etc. [51,[58][59][60][61][62][63][64][65][66][67][68] Reminiscent of collagen processing, [69] the approach delineated herein represents an example of hierarchical self-assembly in which each stage involves building blocks of increasing size such that the resulting supramolecular structure spans over six orders of magnitude, from nanometer-sized covalent building blocks to millimeter calcite wires.…”
mentioning
confidence: 99%